Adsorption of Reactive Black 5 from aqueous solution by cross-linked chitosan/oil palm ash composite beads - Masitah, Hasan (Universiti Teknologi Malaysia (UTM), 2011)
Second International Conference and Workshops on Basic and Applied Sciences (2nd ICOWOBAS) and Regional Annual Fundamental Science Seminar (RAFSS 2009), organized by Universiti Teknologi Malaysia from 2nd - 4th June 2009 at The Zone Regency Hotel, Johor Bahru, Johor.